Does Use of a Feeding Protocol Change Outcomes in Gastroschisis? A Report from the Midwest Pediatric Surgery Consortium - Dekonenko, Charlene; Fraser, Jason D.; Deans, Katherine; Fallat, Mary E.; Helmrath, Michael; Kabre, Rashmi; Leys, Charles M.; Burns, R Cartland; Corkum, Kristine; Dillon, Patrick A.; Downard, Cynthia; Wright, Tiffany N.; Gadepalli, Samir K.; Grabowski, Julia; Hernandez, Edward; Hirschl, Ronald; Johnson, Kevin N.; Kohler, Jonathan; Landman, Matthew P.; Landisch, Rachel M.; Lawrence, Amy E.; Mak, Grace Z.; Minneci, Peter; Rymeski, Beth; Sato, Thomas T.; Slater, Bethany J.; Peter, St. Shawn D. (European Journal of Pediatric Surgery, 2020)
Introduction Gastroschisis feeding practices vary. Standardized neonatal feeding protocols have been demonstrated to improve nutritional outcomes. We report outcomes of infants with gastroschisis that were fed with and without a protocol.Materials and Methods A retrospective study of neonates with uncomplicated gastroschisis at 11 children's hospitals from 2013 to 2016 was performed.Outcomes of infants fed via institutional-specific protocols were compared with those fed without a protocol. Subgroup analyses of protocol use with immediate versus delayed closure and with sutured versus sutureless closure were conducted.Results Among 315 neonates, protocol-based feeding was utilized in 204 (65%) while no feeding protocol was used in 111 (35%). There were less surgical site infections (SSI) in those fed with a protocol (7 vs. 16%, p = 0.019). There were no differences in TPN duration, time to initial oral intake, time to goal feeds, ventilator use, peripherally inserted central catheter line deep venous thromboses, or length of stay. Of those fed via protocol, less SSIs occurred in those who underwent sutured closure (9 vs. 19%, p = 0.026). Further analyses based on closure timing or closure method did not demonstrate any significant differences.Conclusion Across this multi-institutional cohort of infants with uncomplicated gastroschisis, there were more SSIs in those fed without an institutional-based feeding protocol but no differences in other outcomes.
Keywords: gastroschisis; feeding protocol; neonatal feeding